UMKM Naik Kelas dengan Marketing 4.0 - Ahmad Luthfi Hutasuhut (Jurnal Pengabdian Masyarakat Inovasi, 2022)
Product marketing becomes the main obstacle for msme actors in industry 4.0. MSME actors have not known much about digital marketing, especially MSME actors in the area. Especially in the current pandemic, msme actors increasingly feel the impact that is so significant.The purpose of community service is intended so that business people in MSMEs can better understand the use of social media in doing digital marketing. The target achieved in this service is to increase knowledge and understanding in the use of social media for the marketing of their products and businesses so that it is expected that there can be an increase in business income and product revenue in the form of culinary and service incorporated in the padangsidimpuan state-owned house community and able to understand well the procedures for using social media so that it can gain wider market share and more able to compete with existing competitors.The method used is to provide socialization about the procedures for using social media and provide knowledge, understanding and skills of social media utilization in digital marketing. Sharing methods and lectures from BUMN Rumah Konsultan Padang Sidimpuan and evaluating explanations of social media usage procedures and several explanations of the digital economy as part of the industrial revolution 4.0. Marketing 4.0, moving from traditional to Digital will provide a more tangible assessment to partners of the success of this activity